Evaluation of the nicotine metabolite ratio in smoking patients treated with varenicline and bupropion - Tomaz, Paulo Roberto Xavier; Gonçalves, Thuane Sales; Santos, Juliana Rocha; Scholz, Jaqueline; Abe, Tânia Ogawa; Gaya, Patrícia Viviane; Figueiredo, Eduardo Costa; de Faria, Henrique Dipe; Martins, Isarita; Pego, Ana Miguel Fonseca; Bismara, Beatriz Aparecida; Yonamine, Maurício; et al. (Frontiers in Pharmacology, 2022)
Background: Smoking is the leading cause of preventable death worldwide. It is responsible for several types of cancer, cardiovascular diseases, and diseases of the reproductive system, among others. Therefore, advances in research are increasingly necessary in order to make smoking cessation treatment more effective. Some studies have investigated the association of the nicotine metabolite ratio (NMR) with general characteristics and treatment outcomes. In the present study, the main aim was to evaluate the NMR in smoking patients from an Assistance Program of a tertiary cardiology hospital. Methodology: Serum samples were collected from 185 patients at T0 (while patients were still smoking and before starting pharmacological treatment). Cotinine and hydroxycotinine analytes were measured using liquid-chromatography tandem mass-spectrometry (LC-MS/MS). By looking at the relationship between hydroxycotinine and cotinine, we can obtain the NMR, with which it is possible to classify patients into slow metabolizers (NMR < 0.31), as well as normal or fast metabolizers (NMR ≥ 0.31). Results: From 185 patients, 55 were considered slow metabolizers and 130 as normal/fast. The metabolite averages were associated with the number of cigarettes smoked per day (p < 0.001 for cotinine and 0.023 hydroxycotinine). However, we were unable to analyze the association of the NMR with general and clinical characteristics of patients under smoking cessation treatment. Conclusion: We were able to evaluate the NMR, and to observe categories of metabolizers in Brazilian patients under pharmacological treatments. Thus, this study can contribute to the indication of a form of analysis, which might form part of the customization of smoking cessation treatments and, consequently, improve the success rates.